Dynamic modelling of a bolted disc rotor assembly - Blignaut, Gert (My University, 2008)
A project investigating the behaviour of an assembled preloaded rotor was performed for an M-Tech qualification in the Mechanical Engineering Department. Pre-Stressing of mechanical structures is widely applied to improve their performance, and in this project the behaviour of an assembled preloaded rotor was investigated. An Impact Test was done on the structure to see if induced stresses originated by a set of bolts which keep the discs system together, would influence the natural dynamic response or the rotor. Tendencies in the natural response were investigated. Analytical models like the Finite Element Beam model and the Solid Finite Element model were studied in order to find a represntative description of this particular structure's dynamic behaviour after pre-tension. From the experimental results it was apparent that the slenderness of the pre-tensioned sector influences the natural frequency. The solid finite element model appears to be the most applicable model to present the assembled rotor-disk system as a continuous shaft. Furthermore, modelling and predictions for a typical rotor and similar assembled structures can be generated from the findings.
M. Tech. (Department of Mechanical Engineering, Faculty of Engineering and Technology), Vaal University of Technology
Keywords: Assembled pre-loaded rotor; Pre-stressing; Rotor; Impact test; Finite Element Beam; Solid finite element; Induced stresses; 621.82; Rotors